Pengalaman Kader Kesehatan Dalam Penatalaksanaan Posyandu Pada Masa Pandemi Covid-19 Di Desa Arjuna - Ayu Imas Kartika Eka Paksi; Vinami Yulian (CV. Multi Kreasi Media, 2022)
At the end of 2019, Corona Virus Disease (COVID-19) appeared in Wuhan, China, and cases continue to increase in various countries. According to the WHO, the Corona Virus can cause illnesses ranging from mild flu to respiratory infections. This has an impact on various aspects of health services, one of which is maternal and child health services. During the pandemic, services at the Integrated Service Post (Posyandu) had stopped. The posyandu implementation model is carried out independently and handed over to each region according to the COVID-19 zone. The purpose of this study was to determine the experience of health cadres in managing posyandu during the COVID-19 pandemic in Arjuna Village. This type of qualitative research uses an exploratory approach. The population in this study were all health cadres at the posyandu in Arjuna Village. Participants in this study revealed that seven participants were selected using a purposive sampling technique. Collecting research data using interview guidelines and data analysis using verbatim transcripts. The results of the verbatim transcript have three themes, namely (1) knowledge and awareness, (2) the influence of the pandemic on posyandu services, and (3) supporting factors and based on barriers to posyandu services. The results of this study can be an important source of information for health cadres and policy makers in an effort to improve posyandu service activities during the COVID-19 pandemic.